Plug and rubber molded article

A rubber plug with a composition of ethylene propylene diene polymer, chloroprene polymer, and oil, addresses processability and adhesion issues, ensuring reliable sealing and coating adhesion in vehicle body through holes.

JP2025002134APending Publication Date: 2025-01-09INOAC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023102078
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2025-01-09

AI Technical Summary

Technical Problem

Rubber products containing chloroprene polymers have poor processability and adhesion to rust preventive agents, leading to issues during deburring and potential peeling of the rust preventive coating.

Method used

A rubber plug composed of a rubber manufacturing composition containing ethylene propylene diene polymer, chloroprene polymer, and oil, with a high oil content and optional carbon black, to enhance adhesion and processability.

Benefits of technology

The plug achieves improved adhesion to rust preventive agents and enhanced processability, preventing peeling and ensuring effective sealing of through holes in vehicle bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025002134000001_ABST
    Figure 2025002134000001_ABST
Patent Text Reader

Abstract

To provide a plug which has adhesion to a rust inhibitor and further has improved processability.SOLUTION: The plug according to the present disclosure is a rubber plug for closing a through hole of a vehicle and is formed from a composition for rubber production containing an ethylene-propylene-diene polymer, a chloroprene polymer, and an oil. The composition for rubber production contains 40 pts.wt. or more of the oil based on 100 pts.wt. of the total of the ethylene-propylene-diene polymer and the chloroprene polymer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a rubber plug that plugs a through hole formed in a metal plate used in a vehicle body, and to a rubber molded product. [Background technology]

[0002] A through hole is formed in a plate-shaped metal used in a vehicle body, such as an underpanel of an automobile, and this through hole is used during painting, etc. More specifically, during painting, the underpanel, etc. is immersed in a paint tank filled with paint. Then, when the underpanel is removed from the paint tank, the paint flows out from the through hole, and the subsequent processing is performed. In this way, the through hole is used during painting, but if this through hole is left open, dust, water, noise, etc. will enter the inside of the vehicle through the through hole. For this reason, as described in the following Patent Document 1, the through hole is blocked with a rubber plug before the vehicle is shipped.

[0003] Patent Document 1 discloses a plug for closing a through hole, which is molded from a blended rubber of ethylene propylene rubber and chloroprene rubber, and which suppresses the shrinkage of the plug when an underpanel or the like dries, improves ozone resistance, weather resistance, etc., and also improves adhesion to a rust inhibitor (paragraph 0007). Polyvinyl chloride-based rust inhibitors are generally used as rust inhibitors, and the SP value of polyvinyl chloride is close to the SP value of chloroprene rubber. The plug disclosed in Patent Document 1 contains chloroprene rubber, thereby improving adhesion to the rust inhibitor. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-10667 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, rubber products containing chloroprene polymers have poor processability due to their elasticity. In particular, when punching out a product with a die during deburring, small pieces of burrs may remain or parts of the product may be chipped. In order to improve processability, it is possible to reduce the content of chloroprene polymer, but it is not possible to obtain the expected processability by simply reducing the amount of chloroprene polymer (see the present application, Comparative Example 1, and Comparative Example 2). In addition, there is a concern that reducing the content of chloroprene polymer may reduce adhesion to rust inhibitors. In view of the above, an object to be achieved by the present disclosure is to provide a plug which has adhesion to a rust inhibitor and further has improved workability. [Means for solving the problem]

[0006] In order to solve the above problems, the plug according to the present disclosure is a rubber plug for sealing a through hole in a vehicle, and is formed from a composition for manufacturing rubber containing an ethylene propylene diene polymer, a chloroprene polymer, and oil, and the composition for manufacturing rubber contains 40 parts by weight or more of oil per 100 parts by weight in total of the ethylene propylene diene polymer and the chloroprene polymer.

[0007] In addition, in order to solve the above problems, the rubber molded product according to the present disclosure is formed from a rubber manufacturing composition containing an ethylene propylene diene polymer, a chloroprene polymer, and an oil, and the rubber manufacturing composition contains 40 parts by weight or more of oil per 100 parts by weight of the total of the ethylene propylene diene polymer and the chloroprene polymer. Effect of the Invention

[0008] According to the present disclosure, it is possible to provide a plug and a rubber molded product which have adhesion to a rust inhibitor and further improved processability. [Brief description of the drawings]

[0009] [Figure 1] 1 is a table showing the compounding amounts (weight ratios) of compositions for rubber production in Examples 1 to 3 and Comparative Examples 1 and 2. [Diagram 2] 1 is a table showing the content ratios (weight ratios) of polymer, chloroprene polymer, ethylene propylene diene polymer, paraffin oil, and carbon black relative to the total compounded amounts of compositions for producing rubber in Examples 1 to 3 and Comparative Examples 1 and 2. [Diagram 3] 1 is a table showing the vulcanization evaluation, physical property evaluation and various test results of rubber products formed from the rubber production compositions of Examples 1 to 3 and Comparative Examples 1 and 2. [Figure 4] FIG. 2 is a diagram showing traces of plugs formed from the rubber manufacturing compositions of Examples 1 to 3 and Comparative Examples 1 and 2 and punched out with a punching die for removing burrs. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The "plug" according to the present disclosure is used as a rubber plug for blocking a through hole formed in a plate-shaped metal used in a vehicle body. Examples of plate-shaped metal used in a vehicle body include an underpanel. When painting the underpanel, the underpanel is immersed in a paint tank filled with paint. When the underpanel is removed from the paint tank, the paint flows out from the through hole. A rust inhibitor is applied to the underpanel removed from the paint tank, and a drying process is performed. Through this process, the underpanel is painted. Since the through hole is formed to allow the paint to flow out, the through hole is blocked by a plug after the paint has flowed out.

[0011] The timing for closing the through-hole with a plug is preferably after the paint has flowed out of the through-hole and before the rust inhibitor is applied. By closing the through-hole with a plug at this timing, the plug is covered with a coating of the rust inhibitor, making it possible to reliably prevent water and the like from entering the vehicle. However, if the adhesion between the plug and the coating of the rust inhibitor is weak, the coating of the rust inhibitor may peel off from the plug. For this reason, it is desirable to employ a plug that has a high adhesion to the coating of the rust inhibitor.

[0012] In view of this, the "plug" is formed from a rubber manufacturing composition containing an ethylene propylene diene polymer, a chloroprene polymer, and oil. That is, the "plug" is formed as a blend rubber of an ethylene propylene diene polymer (EPDM) obtained by a terpolymer of ethylene, propylene, and diene, and a chloroprene polymer (CR) obtained by polymerization of chloroprene.

[0013] In the "plug" according to the present disclosure, a chloroprene polymer is used, which has an SP value close to that of polyvinyl chloride-based rust inhibitors that are commonly used as rust inhibitors, taking into consideration the adhesion with the rust inhibitor coating. This increases the adhesion between the blended rubber and the rust inhibitor coating, preventing the rust inhibitor coating from peeling off from the plug.

[0014] On the other hand, the "plug" according to the present disclosure has a higher oil (softener) content than the plug disclosed in Patent Document 1. Rubber products containing chloroprene polymers are generally difficult to process. However, by increasing the amount of oil, the processability can be improved. At the same time, the plug can have good adhesion to a coating film of a rust inhibitor. Furthermore, in order to improve the processability, the "plug" according to the present disclosure may have a higher carbon black content than the plug disclosed in Patent Document 1. In this way, by adjusting the amount of oil or carbon black, the "plug" according to the present disclosure can further improve the processability of the plug while maintaining desired physical properties.

[0015] In the "plug" according to the present disclosure, the blending amount of the chloroprene polymer is not specifically limited, but may be at least 5 parts by weight, 10 parts by weight, 15 parts by weight, or 20 parts by weight, relative to 100 parts by weight in total of the ethylene propylene diene polymer and the chloroprene polymer. Alternatively, it may be 10 to 90 parts by weight, 15 to 85 parts by weight, or 20 to 80 parts by weight. Chloroprene polymer is expensive, and the smaller the amount of chloroprene polymer, the more cost can be reduced, so a smaller amount is preferable.

[0016] The oil used as a raw material for the "plug" may be any oil generally used in the manufacture of blended rubber, and may be, for example, naphthenic oil, paraffin oil, aromatic oil, rapeseed oil, or ester-based plasticizers such as dioctyl phthalate. In addition, paraffin oil is preferred in consideration of the amount of volatilization of the oil component during drying treatment at the time of painting. The oil is contained in an amount of 5 to 100 parts by weight, preferably 20 to 100 parts by weight, more preferably 40 to 100 parts by weight, even more preferably 50 to 100 parts by weight, and particularly preferably 55 to 90 parts by weight, per 100 parts by weight of the total of the ethylene propylene diene polymer and the chloroprene polymer. If the amount is 40 parts by weight or more, the blended rubber can be sufficiently softened, and this is preferable.

[0017] The carbon black used as the raw material for the "plug" is preferably contained in an amount of 60 parts by weight or more per 100 parts by weight of the total of the ethylene propylene diene polymer and the chloroprene polymer, more preferably 65 to 200 parts by weight, and further preferably 70 to 150 parts by weight.

[0018] Furthermore, as raw materials for the "plug", reinforcing materials, softeners, vulcanization accelerators (vulcanizing agents), antioxidants, fillers, adhesion promoters, peptizing agents, colorants, lubricants, release agents, flame retardants, and the like can be appropriately added to the rubber manufacturing composition according to the present disclosure.

[0019] As described above, the rubber manufacturing composition for forming the "plug" according to the present disclosure contains an ethylene propylene diene polymer, a chloroprene polymer, and an oil. Furthermore, carbon black may be added, and rubber compounding agents may be appropriately added as necessary.

[0020] Incidentally, the physical properties of the “plug” according to the present disclosure, when measured in accordance with JIS standards, are preferably within the following ranges. The hardness (type A) measured according to JIS K6253-3:2023 is preferably 50 to 70, more preferably 52 to 68, further preferably 54 to 66, and particularly preferably 60±3. The tensile strength, as measured according to JIS K6251:2017, is preferably 6 MPa or more, more preferably 8 to 20 MPa, even more preferably 10 to 18 MPa, and particularly preferably 10±2 MPa. The elongation, as measured according to JIS K6251:2017, is preferably 250% or more, more preferably 300 to 1000%, and even more preferably 400 to 850%. The specific gravity, as measured according to JIS K6268:1998, is preferably 0.5 to 1.5, more preferably 0.8 to 1.4, and even more preferably 1.0 to 1.3. The tear strength, measured according to JIS K6252-1:2017, is preferably 45 N / mm or less, more preferably 25 to 43 N / mm, and even more preferably 30 to 42 N / mm.

[0021] Furthermore, taking into consideration the drying process during painting, it is desirable that changes in the physical properties of the plug due to heating be minimal. Specifically, it is desirable that changes in the hardness, tensile strength, and elongation of the plug due to heating be minimal. The hardness of the plug before heating and the hardness of the plug heated at 70°C for 72 hours are measured in accordance with JIS K6253-3:2023, and the absolute value of the difference between the measured hardness of the plug before heating and the hardness of the plug after heating is calculated using the following formula (1). The calculated value (hardness change) is preferably 8 or less, more preferably 5 or less, and even more preferably 2 or less. It is preferably close to 0. Hardness change (points) = |Hardness after heating - Hardness before heating| (1)

[0022] The tensile strength of the plug before heating and the tensile strength of the plug heated at 70°C for 72 hours are measured in accordance with JIS K6251:2017. Then, the absolute value of the ratio of the difference between the tensile strength of the plug before heating and the tensile strength of the plug after heating to the measured tensile strength before heating is calculated using the following formula (2). The calculated value (rate of change) is preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less. It is preferably close to 0%. Tensile strength change rate (%) = |(tensile strength after heating - tensile strength before heating) / tensile strength before heating x 100| (2)

[0023] The elongation of the plug before heating and the elongation of the plug heated at 70°C for 72 hours are measured in accordance with JIS K6251:2017. Then, the absolute value of the ratio of the difference between the elongation of the plug before heating and the elongation of the plug after heating to the measured elongation before heating is calculated using the following formula (3). The calculated value (rate of change) is preferably 35% or less, more preferably 20% or less, and even more preferably 10% or less. It is preferably close to 0%. Elongation change rate (%) = |(elongation after heating - elongation before heating) / elongation before heating x 100| (3)

[0024] The compression set is 50% or less, preferably 40% or less, and more preferably 30% or less.

[0025] In addition, in the "plug" according to the present disclosure, adhesion strength (N / 10 mm) is adopted as a value that indicates the adhesion strength between the plug and the coating film of the rust inhibitor. More specifically, a rubber plate is molded from the composition for manufacturing rubber according to the present disclosure. A polyvinyl chloride-based rust inhibitor is applied to the molded rubber plate in a thickness of 1 mm over a predetermined area (20 mm x 100 mm) or more. The rubber plate coated with the rust inhibitor is heated in a thermostatic chamber at 155°C for 50 minutes, and is left for two days after heating. After being left for two days, the coating film of the rust inhibitor applied to the rubber plate is cut into a strip of 10 mm width. Then, an end of the strip-shaped coating film is peeled off from the rubber plate, and the end is set in an autograph. Next, the strength (N / 10 mm) when the end of the coating film is pulled in a direction of 180° to the rubber plate at a speed of 50 mm / min is measured by the autograph. This strength (N / 10 mm) is the adhesion strength (N / 10 mm) which indicates the adhesion strength between the plug and the rust inhibitor coating film. A higher adhesion strength (N / 10 mm) value indicates a higher adhesion strength between the plug and the rust inhibitor coating film, and the adhesion strength should be at least 0.74 N / 10 mm or more, and preferably 0.8 N / 10 mm or more. More specifically, it is preferably 0.9 N / 10 mm or more, and particularly preferably 1.0 N / 10 mm or more. The surface of the rubber plate used when measuring the adhesion strength (N / 10 mm) is smooth. In other words, the cavity surface of the mold used when molding the rubber plate is not subjected to a blast treatment.

[0026] Although the "plug" according to the present disclosure has been described above, the rubber molded product formed from the rubber manufacturing composition according to the present disclosure is not limited to the "plug". The rubber molded product according to the present disclosure is suppressed from shrinking due to heating, has ozone resistance and weather resistance, has good adhesion to polyvinyl chloride coatings, and is excellent in processability, and can be used in a wide range of applications. In particular, it is optimal for applications requiring a rubber hardness (type A) of around 60. EXAMPLES

[0027] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples and can be practiced in various forms with various modifications and improvements based on the knowledge of those skilled in the art.

[0028] <Rubber manufacturing composition (raw material)> Plugs of Examples 1 to 3 and Comparative Examples 1 and 2 were produced from the rubber manufacturing composition having the compounding shown in Fig. 1. Details of each raw material are shown below.

[0029] Ethylene propylene diene polymer: SUPRENE 512F, made by Ningbo SK Chloroprene polymer: DCR-71, manufactured by Denka Carbon black: SPHERON SO, manufactured by CABOT (Tianjin) Paraffin oil: PS-430, manufactured by Idemitsu Kosan Vulcanization aid 1: Zinc oxide 40% + CaCO360%, META-Z L-40, manufactured by Inoue Lime Industry · Vulcanization aid 2; Magnesium oxide 1000, manufactured by Kyowa Chemical Industry Co., Ltd. Processing aid 1: Camellia stearate, NOF Corp. Processing aid 2: Homogenizer, STRUKTOL 60NS FRAKES, manufactured by Schill+Seilacher Accelerator 1: Approximately 70wt% zinc dibenzyldithiocarbamate, ZBEC-70GE F140, manufactured by Actmix Vulcanization accelerator 2: Sanmix M-75E, manufactured by Sanshin Chemical Industry Co., Ltd. Vulcanization accelerator 3: TBzTD-70GE F140, manufactured by Actmix Vulcanization accelerator 4: Rhenogran ETU-80, manufactured by RheinChemie Vulcanization accelerator 5: S-80GE F200, manufactured by Actmix

[0030] The raw materials of the rubber manufacturing composition except for the vulcanization accelerators 1 to 5 were weighed out in the composition (weight ratio) shown in FIG. 1 and fed into a kneader for kneading. Then, the mixture was kneaded at 80 to 100°C for 6 minutes. Also, the vulcanization accelerators 1 to 5 were weighed out in the composition (weight ratio) shown in FIG. 1. The weighed vulcanization accelerators 1 to 5 were fed into the kneaded raw materials, and mixed with a rubber roll for 4 to 5 minutes so that the vulcanization accelerators 1 to 5 were dispersed. This produces a rubber material containing the vulcanization accelerator. Then, the rubber material containing the vulcanization accelerator was poured into a predetermined mold and heated for a predetermined time to mold plugs of Examples 1 to 3 and Comparative Examples 1 and 2.

[0031] <Degree of vulcanization evaluation> The raw materials to which the vulcanization accelerators 1 to 5 were added were subjected to a vulcanization degree evaluation. Specifically, the Mooney viscosity of the raw materials of Examples 1 to 3 and Comparative Examples 1 and 2 was measured according to JIS K6300-1. For the measurement, an SMV-300 manufactured by Shimadzu Corporation was used. The Mooney viscosity is an index of the moldability of the raw material. The measurement conditions were ML1+4 at 125°C (1 minute preheating after sample filling (rotor not rotating), viscosity 4 minutes after the rotor started rotating). Furthermore, the Mooney scorch time (min) was measured according to JIS K6300-1. t5 is the time (min) at which the Mooney viscosity has increased by 5 from the minimum Mooney viscosity Vm after the rotor starts rotating. Note that 100 Mooney = 8.3 N m. These measurements are shown in the "Mooney Scorch" column of Figure 3.

[0032] Furthermore, a curing test was carried out on the raw materials of Examples 1 to 3 and Comparative Examples 1 and 2 according to JIS K6300-2. For the measurement, an Orientec Curastometer WR was used. Specifically, the time required for the rate of vulcanization to progress in 8 minutes at 170°C was measured. The time required for 10% vulcanization to progress was T10 (min), and the time required for 90% vulcanization to progress was T90 (min). The measured values ​​are shown in the "Curast" column in FIG. 3.

[0033] <Physical property evaluation> Since it is difficult to evaluate the physical properties of the plug shape, rubber sheets of Examples 1 to 3 and Comparative Examples 1 and 2 were molded using the raw materials of Examples 1 to 3 and Comparative Examples 1 and 2. In detail, the rubber material containing the vulcanization accelerator produced as described above was poured into a mold having dimensions of 110 mm length x 110 mm width x 2 mm depth. Then, vulcanization was performed for 10 minutes under a condition of 170°C. In this way, a rubber sheet to be used for the physical property evaluation was molded. Three of these rubber sheets were stacked, and the physical properties of the three-layer rubber sheet were evaluated by the following method.

[0034] The hardness (points) of the rubber sheets of Examples 1 to 3 and Comparative Examples 1 and 2 was measured in accordance with JIS K6253-3: 2023. The measured values ​​are shown in the "Hardness" column of FIG.

[0035] The tensile strength (MPa) of the rubber sheets of Examples 1 to 3 and Comparative Examples 1 and 2 was measured in accordance with JIS K6251: 2017. The measured values ​​are shown in the "Tensile strength" column in FIG.

[0036] The elongation (%) of the rubber sheets of Examples 1 to 3 and Comparative Examples 1 and 2 was measured in accordance with JIS K6251: 2017. The measured values ​​are shown in the "Elongation" column of FIG.

[0037] The specific gravity of the rubber sheets of Examples 1 to 3 and Comparative Examples 1 and 2 was measured in accordance with JIS K6268: 1998. The measured values ​​are shown in the "Specific Gravity" column in FIG.

[0038] The tear strength (N / mm) of the rubber sheets of Examples 1 to 3 and Comparative Examples 1 and 2 was measured in accordance with JIS K6252-1: 2017. The measured values ​​are shown in the "Tear strength" column in FIG.

[0039] The hardness change (point) of the rubber sheets of Examples 1 to 3 and Comparative Examples 1 and 2 was measured. This hardness change is the hardness change after the rubber sheet is heated at 70°C for 72 hours. That is, the hardness (point) of the rubber sheet heated at 70°C for 72 hours and the hardness (point) of the rubber sheet before heating are measured according to JIS K6253-3:2023, and the difference between the hardness (point) of the rubber sheet after heating and the hardness (point) of the rubber sheet before heating is calculated. The calculated value is the hardness change (point). The calculated value is shown in the "hardness change" column of FIG. 3.

[0040] The tensile strength change rate (%) of the rubber sheets of Examples 1 to 3 and Comparative Examples 1 and 2 was measured. This tensile strength change rate is the change rate of the tensile strength after the rubber sheet is heated at 70°C for 72 hours. That is, the tensile strength (%) of the rubber sheet heated at 70°C for 72 hours and the tensile strength (%) of the rubber sheet before heating are measured according to JIS K6251:2017. Then, the tensile strength (%) of the rubber sheet before heating is subtracted from the tensile strength (%) of the rubber sheet after heating, and the ratio of the subtracted value to the tensile strength (%) of the rubber sheet before heating is calculated. The calculated value is the tensile strength change rate (%). The calculated value is shown in the "tensile strength change rate" column in FIG. 3.

[0041] The elongation change rate (%) of the rubber sheets of Examples 1 to 3 and Comparative Examples 1 and 2 was measured. This elongation change rate is the change rate of elongation after the rubber sheet is heated at 70°C for 72 hours. That is, the elongation (%) of the rubber sheet heated at 70°C for 72 hours and the elongation (%) of the rubber sheet before heating are measured according to JIS K6251:2017. Then, the elongation (%) of the rubber sheet before heating is subtracted from the elongation (%) of the rubber sheet after heating, and the ratio of the subtracted value to the elongation (%) of the rubber sheet before heating is calculated. The calculated value is the elongation change rate (%). The calculated value is shown in the "Elongation change rate" column in FIG. 3.

[0042] The compression set (%) of the rubber test pieces of Examples 1 to 3 and Comparative Examples 1 and 2 was measured. Specifically, the rubber test pieces were compressed to a thickness of 75% of the thickness before compression and left at 70°C. After leaving for 24 hours, the compression set of the rubber test pieces was measured according to JIS K6262. The measured value is shown in the "Compression Set" column in FIG. 3. The rubber test pieces used to measure the compression set (%) are different from the rubber sheets used in the evaluation of other physical properties, and are vulcanized at 170°C for 20 minutes.

[0043] <Molded product evaluation> The adhesion strength (N / 10 mm) of the rubber sheets of Examples 1 to 3 and Comparative Examples 1 and 2 was measured. That is, the adhesion strength between the rubber sheets of Examples 1 to 3 and Comparative Examples 1 and 2 and the coating film of the rust inhibitor was measured according to the above-mentioned method. The measured values ​​are shown in the "UBC adhesion strength" column in Figure 3. The following underbody coat (UBC) was used as the rust inhibitor. 1.366, Sundien366 Parker Asahi

[0044] The plugs of Examples 1 to 3 and Comparative Examples 1 and 2 were observed for bleeding at low temperatures. The plugs were placed in a -40°C environment for 24 hours, and visually inspected to see if compounding ingredients migrated to the rubber surface and crystallized or oozed out as a liquid. If bleeding occurred, it was judged as "NG", and if not, it was judged as "OK". The results are shown in the "Low temperature bleeding" column in Figure 3.

[0045] The workability (ease of finishing) of the rubber sheets of Examples 1 to 3 and Comparative Examples 1 and 2 was evaluated. That is, for the plugs of Examples 1 to 3 and Comparative Examples 1 and 2, the appearance of the plug was visually checked after deburring, and it was evaluated whether small pieces of burr remained around the plug or whether there were any chips. Those without abnormal appearance were rated as "◯: excellent", those with little burr (length 1 mm or less) were rated as "△: acceptable", and those with large burr or chips were rated as "×: unacceptable" (see FIG. 4). Moreover, those with a mixture of "◯" and "△" were rated as "△ to ◯: good". The results are shown in the "Workability (finishing)" column of FIG. 3.

[0046] From the above evaluation results, first, in Comparative Example 1, the blending amounts of polymer, carbon black, and paraffin oil were the same as those in Example 6 of Patent Document 1, and the processability of the plug of Comparative Example 1 was evaluated as "X." In the plug of Comparative Example 2, in which the content of chloroprene polymer was reduced from the blending of Comparative Example 1, the processability was slightly improved, but the processability was evaluated as "Δ." Thus, the desired processability could not be obtained by simply reducing the amount of chloroprene polymer from the raw material.

[0047] When the comparative example 2 is compared with the examples 1 to 3, the processability is further improved, and plugs without abnormalities in appearance after deburring (i.e., "Good") can be obtained, even though the compounding ratio of the polymer is the same. Furthermore, when the adhesion strength of the plugs of the comparative example 2 is compared with that of the examples 1 to 3, although the adhesion strength was slightly decreased in some cases, the adhesion strength was sufficiently within a preferable range. Thus, it is found that the plugs formed from the compositions for rubber production of the examples 1 to 3 have adhesion to the rust inhibitor and are excellent in processability.

[0048] Other physical properties of Examples 1 to 3 do not change significantly, and it can be said that they have the same performance as Comparative Example 2. In particular, when the blending ratio of the polymers is the same as that of Comparative Example 2, the content of the chloroprene polymer can be reduced, and therefore the effect of reducing costs can be fully expected.

[0049] FIG. 2 shows the content ratio (weight ratio) of polymer, chloroprene polymer, ethylene propylene diene polymer, paraffin oil, and carbon black relative to the total compounding amount of the rubber manufacturing composition. In the rubber manufacturing composition according to the present disclosure, it is considered that the processability can be improved by relatively reducing the content of chloroprene polymer by adding a filler, rather than reducing the absolute amount of chloroprene polymer in the total compounding amount. However, there are many different types of fillers that are added to reduce the relative amount. In addition, the addition of a filler may change the original physical properties. The "plug" or "rubber molded product" formed from the rubber manufacturing composition according to the present disclosure is capable of further improving the processability while maintaining the required physical properties.

[0050] Hereinafter, the means for solving the problems of the present application include the following means.

[0051] (1) A rubber plug for sealing a through hole in a vehicle, the plug being formed from a rubber manufacturing composition containing an ethylene propylene diene polymer, a chloroprene polymer, and an oil, the rubber manufacturing composition containing 40 parts by weight or more of the oil per 100 parts by weight of the total of the ethylene propylene diene polymer and the chloroprene polymer.

[0052] (2) The plug according to (1), wherein the rubber manufacturing composition further contains carbon black, and the rubber manufacturing composition contains 60 parts by weight or more of the carbon black per 100 parts by weight in total of the ethylene propylene diene polymer and the chloroprene polymer.

[0053] (3) A rubber molded article, which is formed from a composition for rubber production containing an ethylene propylene diene polymer, a chloroprene polymer, and an oil, wherein the composition for rubber production contains 40 parts by weight or more of the oil per 100 parts by weight of the total of the ethylene propylene diene polymer and the chloroprene polymer.

[0054] (4) The rubber molded product according to (3), wherein the rubber manufacturing composition further contains carbon black, and the rubber manufacturing composition contains 60 parts by weight or more of the carbon black per 100 parts by weight of the total of the ethylene propylene diene polymer and the chloroprene polymer.

Claims

1. A rubber plug for sealing a through hole in a vehicle, an ethylene propylene diene polymer; A chloroprene polymer; and a rubber manufacturing composition comprising: The composition for rubber production contains 40 parts by weight or more of the oil per 100 parts by weight of the total of the ethylene propylene diene polymer and the chloroprene polymer. plug.

2. The rubber making composition further comprises carbon black, The composition for rubber production contains 60 parts by weight or more of the carbon black per 100 parts by weight of the total of the ethylene propylene diene polymer and the chloroprene polymer. The plug according to claim 1.

3. A rubber molded product, an ethylene propylene diene polymer; A chloroprene polymer; and a rubber manufacturing composition comprising: The composition for rubber production contains 40 parts by weight or more of the oil per 100 parts by weight of the total of the ethylene propylene diene polymer and the chloroprene polymer. Rubber molded products.

4. The rubber making composition further comprises carbon black, The composition for rubber production contains 60 parts by weight or more of the carbon black per 100 parts by weight of the total of the ethylene propylene diene polymer and the chloroprene polymer. The rubber molded article according to claim 3.

Citation Information

Patent Citations

  • plug

    JP2015010667A